Peran Perawat sebagai Educator Mempengaruhi Kepatuhan Konsumsi Obat Antiretroviral (ARV) Bagi Pasien HIV/AIDS di Klinik VCT RSUD Dr. Moewardi - Danik Astuti; Mulyaningsih Mulyaningsih (STIKes Patria Husada Blitar, 2016)
HIV/AIDS is a global matter, it threatens the world including Indonesia. Antiretroviral (ARV) is a therapy which patients have to consume medicine for their life, antiretroviral (ARV) therapy is able to make relieved to ODHA (HIV/AIDS patient) and family. Nurse participation is most needed by patients in doing therapy process. The aim of this study was to know and analyze the correlation of nurses as educator by the compliance of antiretroviral medicine consumption to HIV/AIDS patients in VCT clinic of Dr. Moewardi hospital. This research used cross sectional approach. The research subjects were HIV/AIDS patients which undergone antiretroviral (ARV) therapy in VCT clinic of Dr. Moewardi hospital by 65 respondents as sample. The research instruments used questionnaire and follow-up card. The data analysis used chi square test. Result;Univariat analysis outcome was known by most of respondents to perceive nurses participation as educator in good category (58,5%) and most of them are obedient in consuming antiretroviral (ARV) medicine (52,3%). Bivariat analysis outcome was the chi square score to significant extend 5% as 6,665 by ï²value 0,010 and odd ratio (OR) as mush as 3,846 CI 95% (1.354-10.922). There was significant correlation between nurses as educator and the compliance of antiretroviral (ARV) medicine consumption in VCT clinic of Dr. Moewardi hospital.